Shape Effect of Pd-Promoted Ga2O3 Nanocatalysts for Methanol Synthesis by CO2 Hydrogenation - Qu, J; Zhou, X; Xu, F; Gong, X; Tsang, S (American Chemical Society, 2014)
In this paper, we present a new approach to investigate metal-support interaction in catalysis. First, we have carried out a controlled growth of two semiconductive Ga2O3 nanocrystals in distinctive shapes, namely, plate and rod with the majority of their surfaces covered with polar and nonpolar facets, respectively. We have then placed the same contents of Pd on these nanocrystals and carried out a systematic testing and characterization for methanol synthesis from CO2 hydrogenation under industrial applicable conditions. It is found that a low indexed (002) polar Ga2O3 surface is highly unstable, which gives oxygen defects and mobile electrons in the conduction band more readily than those nonpolar (111) and (110) surfaces. A significantly strong metal-support interaction between the (002) polar Ga2O3 surface and Pd was determined, and it gave rise to higher metal dispersion and facilitated electron transfer between them, leading to the formation of PdGax. This renders such composite nanocatalysts active for methanol production.